Serum Endostatin Concentrations Are Higher in Men with Symptoms of Intermittent Claudication. (29th January 2014) - Golledge, Jonathan; Clancy, Paula; Hankey, Graeme J.; Yeap, Bu B.; Norman, Paul E.
Abstract : Objectives . A cleavage fragment of collagen XVIII, endostatin, is released into the circulation and has been demonstrated to have antiangiogenic effects in animal models. We hypothesized that circulating endostatin would be increased in patients with symptoms of lower limb peripheral artery disease. Design . Cross-sectional study. Participants . Community dwelling older men. Measurements . Intermittent claudication was defined using the Edinburgh Claudication Questionnaire (ECQ). Serum endostatin was measured by a commercial ELISA. The association of serum endostatin with intermittent claudication was examined using logistic regression adjusting for age, diabetes, hypertension, dyslipidemia, coronary heart disease, and stroke. Results . Serum endostatin was measured in 1114 men who completed the ECQ. 106 men had intermittent claudication, 291 had atypical pain, and 717 had no lower limb pain. Mean (±standard deviation) serum endostatin concentrations (ng/mL) were 145.22 ± 106.93 for men with intermittent claudication, 129.11 ± 79.80 for men with atypical pain, and 116.34 ± 66.57 for men with no lower limb pain; P < 0.001 . A 70 ng/mL increase in endostatin was associated with a 1.17-fold rise in the adjusted odds of having intermittent claudication (OR 1.17, 95% confidence interval 1.00–1.37, and P = 0.050 ). Conclusions . Serum endostatin is raised in older men who have symptoms of intermittent claudication. The role of endostatin in the genesis and outcome of peripheral artery disease requires further investigation.